The legend of the poinsettia - DePaola, Tomie, 1934-2020- (G.P. Putnams Sons, 1994)
When Lucida is unable to finish her gift for the Baby Jesus in time for the Christmas procession, a miracle enables her to offer the beautiful flower we now call the poinsettia.